Perspektif Epistemologis Teologi Islam Liberal - Halid Al-Kaf (Universitas Islam Negeri Mataram, 2009)
Religious liberalism in Islamic context has many possible meanings: first, the development of rational thought and attitude; second, the freedom to interpret religious texts; third, the belief that all religions encourage virtue and support the universal values of humanity; fourth, strengthening the separation thing what is profane (worldly) from the sacred (religious). The article aims to analyze some of the terms relating to the Liberal Islamic theology, that is: religious liberalism, secularism, secularization, and pluralism. In the aspect of religious texts interpretation, Islamic liberalism has at least three characteristics: first, patterned substantive, that is to understand the religious teachings are not limited to the scriptural reason (text) but rather on finding a more substantial meaning behind the text. Second, patterned contextual, i.e. to interpret religious texts on a variety of contexts. Third, patterned rational, i.e. to interpret religious teachings based on the reasoning/logic of healthy and humanitarian objective.